THE ROLE OF DESTINATION SPATIAL SPILLOVERS AND TECHNOLOGICAL INTENSITY IN THE LOCATION OF MANUFACTURING AND SERVICES' FIRMS - Andrés Artal Tur; José Miguel Navarro Azorín; María Luisa Alamá Sabater; Antonio García Sánchez (European Regional Science Association (ERSA), 2011)
Focusing on the characteristics of destinations, this paper pursues to identify the role of spatial spillovers in driving location choices of manufacturing and services' firms. With this objective a spatial conditional logit framework is defined, allowing for neighbourhood-related spatial effects. Additionally, a broad indicator of spatial spillovers generated by a given destination is proposed. The model is then applied to empirically capture the behaviour of 1.092.864 new firms established in 316 municipalities of the Spanish Mediterranean Arc (SMA) between 1998 and 2008. Estimation results show that such spatial effects have a remarkable impact on the location decisions of industrial companies relative to those of services. When the sample is splitted out by technological intensity of activities, it can be observed that spatial spillovers are more willing to affect decisions of high-tech companies relative to those of low-tech ones, particularly for industrial activities.
Keywords: 330